2012
DOI: 10.1063/1.3678182
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of heavy-hole spin dephasing in (InGa)As quantum dots

Abstract: We measure the spin dephasing of holes localized in self-assembled (InGa)As quantum dots by spin noise spectroscopy. The localized holes show a distinct hyperfine interaction with the nuclear spin bath despite the p-type symmetry of the valence band states. The experiments reveal a short spin relaxation time {\tau}_{fast}^{hh} of 27 ns and a second, long spin relaxation time {\tau}_{slow}^{hh} which exceeds the latter by more than one order of magnitude. The two times are attributed to heavy hole spins aligned… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 10 publications
5
62
0
Order By: Relevance
“…On the other hand, it has been demonstrated experimentally that a probe beam propagating in the region of weak absorption can substantially perturb the spin system. 11 The effect is most pronounced if special techniques, i.e. use of high-extinction polarization geometries and/or placing the sample into the optical cavity are applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been demonstrated experimentally that a probe beam propagating in the region of weak absorption can substantially perturb the spin system. 11 The effect is most pronounced if special techniques, i.e. use of high-extinction polarization geometries and/or placing the sample into the optical cavity are applied.…”
Section: Introductionmentioning
confidence: 99%
“…By now it has already been successfully applied to bulk semiconductors, 5,6 multiple and single quantum well structures, 7,8 individual quantum dots and quantum dot ensembles [9][10][11] making it possible to reveal and analyze spin dynamics of electrons and holes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments have determined the value [59,60] and sign [61] of the hyperfine coupling constants for hole spins and have achieved coherent optical control of the hole spin in single [62,63] and double [64] quantum dots, thus enabling measurements of the relaxation time T 1 [65,66,67], estimates of a bound on the ensemble-averaged free-induction decay time T * 2 [68], and more recently, real-time measurements of T * 2 and the spin-echo decay time, T 2 [62]. In Sec.…”
Section: -Introductionmentioning
confidence: 99%
“…In 2012, SNS studies were reported on quantum dot ensembles whose signal comes from about 50 holes. [6,7] Oestreich et al pushed the SNS technique down to the single spin detection regime and studied the spin relaxation dynamic of a single heavy hole localized in a single (InGa)As quantum dot in 2014. [8] In 2015, SNS was used to study nuclear spin dynamics in n-type GaAs.…”
Section: Introductionmentioning
confidence: 99%